METHODOLOGY FOR DEVELOPING FOREIGN LANGUAGE (ENGLISH) SPEECH COMPETENCE OF NON-LINGUISTIC HUMANITIES STUDENTS BASED ON EDUCATIONAL COMMUNICATIVE-PROJECT ACTIVITIES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The development of foreign language competence, particularly English, is a critical component of higher education for students of non-linguistic humanities disciplines. This study examines the methodology of enhancing students’ English speech competence through communicative-project based educational activities. The research focuses on integrating practical project work with language learning, fostering both productive language skills and intercultural communication abilities.